Analisis Potensi Lingkungan Sekitar Sebagai Sumber Belajar Biologi yang Berdayaguna - Susilo, Mohamad Joko (Universitas Sebelas Maret, 2018)
The environment is an object of unlimited biological studies. However, not every object is the scope of biological studies. To raise the potential of the surrounding environment to be an object of useful biological study needs a series of analysis process first. This study aims to analyze the potential of the surrounding environment that can be used as a biological learning resource. Based on the findings it is found that to raise the environment as a learning resource can be done through the steps: 1) analyzing the curriculum (KI, KD, and learning objectives); 2) ensuring the relevance of the chosen method with consideration; 3) ensuring the relevance of the chosen method with consideration of material characteristics to be taught; 4) determine the characteristics of student development with local geographic background; and 5) to ensure potential sources of learning from the environment by considering the relevance, adequacy, and consistency of the material with the applicable curriculum, the learning objectives to be achieved, and the achievement level of the learning materials.